PERSEPSI DAN MOTIVASI PENGUNJUNG NUSANTARA TAMAN NASIONAL BUNAKEN - Handoyo, Eko Wahyu; Walangitan, Hengki Djemie; Pangemanan, Paulus Adrian (Sam Ratulangi University, 2022)
This study aims to determine perceptions and motivations of domestic visitors to Bunaken National Park. Data collection was carried out during September to November 2021. The research method used was a survey method with a sample of respondents taken randomly, using a purposive sampling of 150 people. The results showed that the characteristics of visitors were evenly distributed in all ages in the age range of 21-25 years, dominated by Bachelor and Senior High School, professions of private employees, entrepreneurs and civil servants, income between Rp 1.000.000,- – Rp 2.000.000 to more than Rp 5.000.000 and the number of family members between 3 - 5 people. The perception of visitors is attractive as much as 44.7% and very attractive 37.3%, the value being very important is 62.7% and important is 27.3%, visitor satisfaction convey 41.3% satisfied and 40.7% very satisfied. The motivation of visitors because of the advantages Bunaken National Park 35% a good natural tourist destination, 21% near to Manado City and 17% cheap and easy accessibility, as a reference source of visiting information 38% comes from stories of friends, 24% social media facebook, 15.3% social media instagram and 12.7% websites.